WAVE MODELLING OF A LIGHTWEIGHT AEROSPACE PANEL USING A FINITE ELEMENT APPROACH - Sousa, Kleverson C. de; Fabro, Adriano T. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Aerospace structures require high strength and low mass, which has led to an increase in the use of composite materials by its industry. These materials result from theÂ combination of two or more base materials in a way that one or more of the composite’sÂ properties are superior to either of the individual ones. A type of material that presents thoseÂ desired attributes is the honeycomb sandwich panels and, as the industry is relying more andÂ more on them, their accurate characterization for the given application is of extremeÂ importance. In this paper, the wave and finite element (WFE) approach is applied and the wave parameters of a homogenized honeycomb sandwich panel model for aerospaceÂ applications are presented and numerical details discussed. The wave approach differs fromÂ the more usual modal analysis (MA) by focusing in properties such as the dispersionÂ relations, wave modes, phase and group velocities, and energy transmission. Although MAÂ with the aid of finite element modelling (FEM) is a widely used technique, as the frequenciesÂ of interest increase, the computational cost also increases. Moreover, the size of the elementsÂ also limits the maximum frequency that can be accurately characterized. On the other hand,Â the WFE method requires the model of a single period of a periodic structure, which can beÂ obtained from any commercial FE software, benefiting from the available element libraries, reducing the computational cost when applied to a wider frequency range. The numericallyÂ obtained parameters are compared to an analytical model and show agreement with theÂ theory. Keywords: Wave and finite element, Wave propagation, Sandwich panel